O sposobach zapisywania gwary raz jeszcze (na przykładzie tekstów z Zaolzia) .......... 191 - Labocha, Janina; Tutak, Kinga (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
ONCE AGAIN ON THE METHODS OF RECORDING DIALECT (USING THE EXAMPLE OF ZAOLZIE)The paper aims to demonstrate the different methods for recording dialectal spoken utterances in order to preserve them and simultaneously to make them accessible to readers. The article focuses on texts recorded on magnetic tape in 1976 in the town of Sucha Dolna (Havířov/Hawierzów). The second part discusses issues connected with the recording of such texts, a topic explored in the 1950s in the Zaolzie journal “Zwrot” by Leon Derlich (1905–1965), a Polish patriot, resistance fighter, ethnographer, and amateur linguist. The third part of the paper returns to texts from the 1970s, and presents them in two versions tailored for different potential recipients: both those who are familiar with the dialect, and those who encounter it for the first time. It seems that a semi-phonetic transcription of recorded dialectal texts meets the needs of a broader audience, not just specialists: dialectologists or ethnographers. L. Derlich recognized this need and successfully introduced, applied, and perfected such a method for preserving texts from the Cieszyn Silesia region.